2015
DOI: 10.1016/j.nedt.2014.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Translating research into practice: Evaluation of an e-learning resource for health care professionals to provide nutrition advice and support for cancer survivors

Abstract: The project has shown the benefits of interprofessional working to develop an e-learning resource for Health Care Professionals to support cancer survivors in following healthier lifestyles. Positive attitudes and potential improvements in the knowledge base and changes for professional practice were demonstrated. Further research is required to gauge sustained impact in the work environment by embedding the resource as part of CPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
6

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 25 publications
0
25
0
6
Order By: Relevance
“…55 On the other hand, health care providers for cancer patients can obtain valuable up-to-date information through web-based information technologies. [56][57][58][59] Webbased recommender systems are one of the information resources management tools, especially health information, available on the web. 44 A web-based recommender system is a web-based software that offers web pages based on the interests and needs of the users.…”
Section: Web-based Recommender Systemsmentioning
confidence: 99%
“…55 On the other hand, health care providers for cancer patients can obtain valuable up-to-date information through web-based information technologies. [56][57][58][59] Webbased recommender systems are one of the information resources management tools, especially health information, available on the web. 44 A web-based recommender system is a web-based software that offers web pages based on the interests and needs of the users.…”
Section: Web-based Recommender Systemsmentioning
confidence: 99%
“…When the domestic and international studies are examined it is seen that the use of media tools and internet based learning resources have been studied, developed and evaluated, different e-learning models have been introduced and these models have been evaluated in the implementation process, e-learning and face to face learning implementations have been compared in terms of their advantages and limitations (Aydın & Biroğul, 2008;Bañados, 2006;Çakmak & Yılmaz, 2014;Karasar, 2004;Kassens-Noor, 2012;Lahti, Kontio, Pitkänen & Välimäki, 2014;Murphy, Worswick, Pulman, Ford & Jeffery, 2015;Reily, Vandenhouten, Gallagher-Lepak & Ralston-Berg, 2012).…”
Section: Yapılandırılmışmentioning
confidence: 99%
“…There are, however, examples of non-credit bearing specialist nutrition education. Murphy et al, (2015) situated such a module within a national cancer charity website learning zone. A positive evaluation of the module by health professionals led to it being made available to cancer survivors.…”
Section: It Is Critical To the Success Of E-learning That Attention Imentioning
confidence: 99%
“…Importantly, the module could be accessed internationally. Observers of e-learning in healthcare have also found that despite fears about a lack of face-to-face contact and ICT skills, e-learning provides access to education with equally good outcomes (Lahti et al, 2014a and2014b) and opportunity for learning when release from clinical work to attend courses is increasingly difficult (Murphy et al, 2015). E-learning also offers a more flexible learning experience where learners can access materials at times and for durations that fit with their busy professional lives (Forman et al, 2002).…”
mentioning
confidence: 99%